Pengaruh Kepuasan Konsumen Terhadap Kesediaan Membayar (Willingness To Pay) dengan Dimoderasi Reputasi Perusahaan - Kusumastuti, Aprillia Elly; Rizqiana, Fitra (ECONBANK: Journal of Economics and Banking, 2021)
This study aims to analyze the effect of consumer satisfaction on willingness to pay and to analyze the effect of consumer satisfaction on willingness to pay with reputation variable as moderated. The population in this study are consumers who buy Honda motorcycle products at Honda Prima & AHASS Pemalang Motorcycle Dealers. The number of samples is 100 respondents. The sampling technique used was purposive sampling. The purposive sampling technique is a sampling-based on the criteria aimed at by the researcher. The data analysis used in this research is Moderated Regression Analysis. The results showed that consumer satisfaction has a significant effect on willingness to pay for consumers of Honda Prima & AHASS Pemalang Motorcycle Dealers. The company's reputation moderates the effect of consumer satisfaction on willingness to pay on consumers of Honda Prima & AHASS Pemalang Motorcycle Dealers